Features of mechanical pulse treatment of filters and near-filter zones of in-situ uranium leaching wells - A. G. Ivanov; Yu. A. Arsentiev; D. D. Orekhov; R. I. Gavrilov (Известия высших учебных заведений: Геология и разведка, 2025)
Introduction. Uranium mining by in-situ leaching (ISL) requires the use of special methods for developing wells and maintaining their design productivity (flow rate) both at the construction stage and during operation by carrying out repair and restoration work (R&R). The operation of process wells is accompanied by mechanical, chemical or gas colmatation of filters and near-filter zones (PFZ). In this case, various methods are used to remove the colmatant, which complicates under ground leaching, among which are: mechanical, chemical, physical and combined. This article is devoted to the assessment of the efficiency of using three types of mechanical pulse treatment of uranium SPV process wells at production facilities during their development and repair: pneumatic pulse treatment, using hydrovibrators and pneumatic swabbing. Objective. To provide conditions for increasing the operating period of a production well with productivity at the level of design values. Materials and methods. In this paper, the problem is solved by analyzing the physical nature of the processes occurring, characteristic of the three types of mechanical pulse processing of filters being compared and implemented at enterprises and filter zones, as well as a comparison of the effectiveness of the results of their action, the criterion for which was the volume of working solutions containing a useful product extracted to the surface. Results. The studies have shown that the most effective of the mechanical pulse methods under consideration is the processing of filters and PFZ using hydrovibrators. Conclusion. The use of new technical repair means leads to an increase in the efficiency of ore body development.